Structure and crystallization kinetics of lithium tellurite glasses - Ersundu, M. Celikbilek; Ersundu, A. E. (ELSEVIER SCIENCE BV, 2016)
In this work, structure and crystallization kinetics of lithium tellurite glasses were investigated. Thermal stability and glass formation ability was monitored using differential scanning calorimetry through the calculation of temperature difference, Delta T, thermal stability, S, Hruby parameter, H-r and reduced glass transition temperature, T-rg. Physical features of lithium tellurite glasses were investigated in terms of density, rho, molar volume, V-M, oxygen molar volume, V-O, oxygen packing density, number of bonds per unit volume, n(b), and Poisson's ratio, mu(cal) and the structural transformations on the glass network were studied using Fourier transform infrared spectroscopy. The crystallization kinetics was studied under non-isothermal conditions. The values of Avrami constant, n, and morphology index, m were calculated from the Ozawa equation and the activation energy of crystallization, E-C, was determined by modified Kissinger equation. The crystallization behavior of crystallized and/or transformed phases was confirmed by X-ray diffraction and scanning electron microscopy analysis. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Amorphous materials; Kinetics; Microstructure; Lithium tellurite glass; NONISOTHERMAL CRYSTALLIZATION; 20LI(2)O-80TEO(2) GLASS; THERMAL-ANALYSIS; SYSTEM; TEMPERATURE; NUCLEATION; ENERGY; Materials Science